Pemanfaatan Arang Aktif Dari Batubara Kotor (Dirty Coal) Sebagai Adsorben Ion Logam Mn(II) dan Ag(I) - Saibun Sitorus; Meliani Pijer (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. The research has done about use of activated carbon as an adsorben of dirty coal in metal ions Mn(II) and Ag(I). This research was intended to find the effects of pH value, contact period and to determine the maximum adsorptive capacity Mn(II) and Ag(I) metal ions by dirty coal activated carbon. The adsorption process have been variate of pH 2, 3, 4, 5, 6, 7 and 8; contact time variation 15, 30, 45, 60 and 75 minutes; concentration variation 30, 45, 60, 75, 105, and 120 mg/L. The adsorption capacity determinate of Mn(II) and Ag(I) metal ions by dirty coal activated carbon used Isoterm Langmuir. The analysis of metal ions Mn(II) and Ag(I) concentration by dirty coal activated carbon by using atomic absorption spectrophotometer (AAS). The result of this research shows that dirty coal activated carbon could adsorb metal ion Mn(II). The optimum condition was achieved at the pH 6 with a number of metal ions that adsorbed at 23,4265 mg/L, with optimum period of 30 minutes with a number of metal ions that adsorbed at 23,9939 mg/L, as for optimum concentration was achieved at the cosentration 90 mg/L with a number of metal ions that adsorbed at 56,5518 mg/L and metal ion adsorption capacity of Mn(II) adsorbed by the dirty coal activated carbon could reach 34,4827 mg  Mn/g. As for the adsorption of metal ions Ag(I) the optimum condition was achieved at the pH 7 with a number of metal ions that adsorbed at 20,5000 mg/L. Keywords: dirty coal, activated carbon, adsorption, metal ions Mn(II), metal     ions Ag(I)